Fitting MD analysis in an argument-based validity framework for writing assessment: Explanation and generalization inferences for the ECPE. (April 2020) - Yan, Xun; Staples, Shelley
The argument-based approach to validity (Kane, 2013) focuses on two steps: (1) making claims about the proposed interpretation and use of test scores as a coherent, interpretive argument; and (2) evaluating those claims based on theoretical and empirical evidence related to test performances and scores. This paper discusses the role of multidimensional (MD) analysis (Biber, 1988), a corpus analytic approach to examining linguistic and discourse characteristics of language performance, in an argument-based validation framework for writing assessment. We propose a set of warrants, assumptions and evidence for inferential steps pertaining to investigations of performance characteristics in language assessments. Then, we illustrate how MD analysis can provide evidence for generalization and explanation inferences through a case study that examines lexico-grammatical features of writing performances on the Examination for the Certification of Proficiency in English (ECPE).